1989
DOI: 10.1139/v89-270
|View full text |Cite
|
Sign up to set email alerts
|

The electron spin resonance spectra of dioxene radical cations

Abstract: . Can. J. Chem. 67, 1748 (1989).The electron spin resonance spectra of the radical cations of dioxene (la), 2,3-dimethyldioxene (lb), 2,3-diphenyldioxene (lc), and benzodioxane (2) in fluid solution have been observed and analysed, with the help of ENDOR spectroscopy in the case of l c . It is concluded that in l c the molecule has overall C2 molecular symmetry. In all four compounds, the pseudo-axial and pseudo-equatorial protons of the methylene groups in the half-chair dioxene rings are distinguished by dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…
The kinetics of the inversion of the dihydrodioxine ring in the radical cations of six dihydrobenzo [1,4]dioxines have been determined by EPR spectroscopy. In the nine compounds for which results are now available, the activation energies E a range from 22.6 to 47.6 kJ mol Ϫ1 , and the pre-exponential factors, log A, from 12.8 to 16.2.
…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…
The kinetics of the inversion of the dihydrodioxine ring in the radical cations of six dihydrobenzo [1,4]dioxines have been determined by EPR spectroscopy. In the nine compounds for which results are now available, the activation energies E a range from 22.6 to 47.6 kJ mol Ϫ1 , and the pre-exponential factors, log A, from 12.8 to 16.2.
…”
mentioning
confidence: 99%
“…Dihydro [1,4]dioxines can readily be converted into their radical cations, which can be observed by EPR spectroscopy. The ring inversions occur at a rate which can be measured by monitoring the line shape effects on the signals of the axial and equatorial protons over a range of temperatures, and computer simulation of the spectra gives the rate constants and thence the Arrhenius and Eyring parameters for these reactions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Computer simulations provide rate constants and, hence the activation parameters for these reactions. This study is reported for 26-28 [99].…”
Section: H Systemsmentioning
confidence: 96%